On Partial Null Subject languages: Why pro-drop in Brazilian Portuguese and Russian became similar but not identical (Revista de Estudos da Linguagem, 2024)
In this paper, I claim that a parametric view on change in pro-drop does not contradict the fact that not all the Partial Null Subject (PNS) languages display identical properties. I show that the contingent nature of diachronic change is the reason for the slight differences between PNS languages. Modern Russian (MR) and Brazilian Portuguese (BP) are two PNS languages that developed from Consistent Null Subject antecessors (Old Russian and European Portuguese) independently from each other. I account for the change in pro-drop experienced by these two languages, analyzing the properties usually related to the null subject parameter (verbal inflection, clitics, null objects, embedded and arbitrary null subjects), and show that the final parametric setting in both MR and BP was almost identical, with small differences that can be attributed to the different initial conditions for the change.